EFEKTIVITAS GAMIFIKASI DALAM PEMBELAJARAN PAI TERHADAP MOTIVASI BELAJAR GENERASI Z : SYSTEMATIC LITERATURE REVIEW - Sari, Yunita; Koderi, Koderi; Fitriani, Fitriani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze the effectiveness of gamification in Islamic Religious Education (IRE) learning on Generation Z students’ learning motivation in the digital era. The research employed a Systematic Literature Review (SLR) method based on the PRISMA guidelines. Data were collected from various scientific databases, including Scopus, Google Scholar, SINTA, and Publish or Perish, covering publications from 2020 to 2025. Out of 225 identified articles, 16 studies met the inclusion criteria and were analyzed in depth. The findings indicate that gamification in IRE learning is understood as the integration of game elements, such as points, levels, challenges, and reward systems, into the learning process without diminishing Islamic values. Gamification has been proven effective in enhancing students’ learning motivation and interest, participation and engagement, understanding of IRE materials, as well as fostering Islamic attitudes and character development. Commonly applied gamification strategies involve the use of digital platforms and Learning Management Systems (LMS), with teachers playing a key role as instructional designers aligned with pedagogical objectives. However, several challenges were identified, including limited teacher digital competence and inadequate infrastructure. Therefore, educational policy support, infrastructure development, and continuous teacher professional training are essential to optimize the sustainable implementation of gamification in IRE learning within the digital era. ABSTRAK Penelitian ini bertujuan untuk menganalisis efektivitas gamifikasi dalam pembelajaran Pendidikan Agama Islam (PAI) terhadap motivasi belajar generasi Z di era digital. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan mengacu pada pedoman PRISMA. Data diperoleh dari berbagai basis data ilmiah seperti Scopus, Google Scholar, SINTA, dan Publish or Perish dengan rentang publikasi tahun 2020–2025. Dari total 225 artikel yang teridentifikasi, sebanyak 16 artikel memenuhi kriteria inklusi dan dianalisis secara mendalam. Hasil kajian menunjukkan bahwa gamifikasi dalam pembelajaran PAI dipahami sebagai integrasi elemen permainan, seperti poin, level, tantangan, dan sistem penghargaan, ke dalam proses pembelajaran tanpa menghilangkan nilai-nilai keislaman. Penerapan gamifikasi terbukti efektif dalam meningkatkan motivasi dan minat belajar, partisipasi dan keterlibatan peserta didik, pemahaman materi PAI, serta pembentukan sikap dan karakter Islami. Strategi gamifikasi yang banyak digunakan melibatkan pemanfaatan platform digital dan Learning Management System (LMS) dengan peran guru sebagai perancang pembelajaran yang berorientasi pada tujuan pedagogis. Meskipun demikian, penerapan gamifikasi masih menghadapi tantangan berupa keterbatasan kompetensi guru dan sarana prasarana. Oleh karena itu, dukungan kebijakan pendidikan, penguatan infrastruktur, serta peningkatan kompetensi guru menjadi faktor penting dalam mengoptimalkan penerapan gamifikasi dalam pembelajaran PAI di era digital.